2018
DOI: 10.1186/s13047-017-0243-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival and associated risk factors in patients with diabetes and amputations caused by infectious foot gangrene

Abstract: BackgroundInfectious gangrene of the foot is a serious complication of diabetes that usually leads to a certain level of lower-extremity amputation (LEA). Nevertheless, the long-term survival and factors associated with mortality in such patients have yet to be elucidated.MethodsA total of 157 patients with type 2 diabetes who received treatment for infectious foot gangrene at a major diabetic foot center in Taiwan from 2002 to 2009 were enrolled, of whom 90 had major LEAs (above the ankle) and 67 had minor LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 38 publications
4
47
1
1
Order By: Relevance
“…Also, the risk of recurrent infection is the highest for those patients with the most aggressive amputations. 5 Major amputation is associated with a 5-year survival of only 30-40% 6 and a markedly increased the risk of cardiovascular disease. 7 The cost of care of DMO is extraordinary, and a previous study indicated the potential economic benefits of reducing amputations to be $2,900 to $4,442 per person.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk of recurrent infection is the highest for those patients with the most aggressive amputations. 5 Major amputation is associated with a 5-year survival of only 30-40% 6 and a markedly increased the risk of cardiovascular disease. 7 The cost of care of DMO is extraordinary, and a previous study indicated the potential economic benefits of reducing amputations to be $2,900 to $4,442 per person.…”
Section: Discussionmentioning
confidence: 99%
“…The surgery of diabetic foot complications comprises a wide range of interventions, from incisions, debrides, transfalangeal and transmetataral amputations of toe/s or major amputations. Adjunctive treatments, such as: plastic surgery methods for the coverage of skin defects, negative pressure therapy and hyperbaric oxygenotherapy, both with the role of accelerating the process of wound granulation, represent methods that balance the evolution to healing (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Among the plethora of serious diabetes‐related complications, the diabetic foot (DF) is one of the most common, disabling, and costly, which persists as the most frequent cause of non‐traumatic lower‐extremity amputation (LEA). Major (at or above‐the‐ankle) LEAs are a particular catastrophic event, demonstrating an 80% higher mortality than minor amputations and a median survival of only 1.9 years . Major LEAs also result in profound consequences to the health‐related quality of life of the patient and his or her family and caregivers, is a source of psychological distress and scarring, and preludes exceptionally high health care expenditures and homecare costs .…”
Section: Introductionmentioning
confidence: 99%
“…Major (at or above-the-ankle) LEAs are a particular catastrophic event, demonstrating an 80% higher mortality than minor amputations and a median survival of only 1.9 years. 1 Major LEAs also result in profound consequences to the health-related quality of life of the patient and his or her family and caregivers, 2,3 is a source of psychological distress and scarring, 4 and preludes exceptionally high health care expenditures and homecare costs. 5,6 Unfortunately, preventing this unwarranted outcome is often exceptionally challenging because of a constellation of several factors, such as the aggressive and necrotising infection course, compromised arterial supply, patient's comorbidities, and delay in seeking medical care.…”
Section: Introductionmentioning
confidence: 99%